Copyright Violation and Distribution of Prohibited Content on the Internet: Analysis of Legal Arrangements in the Legislation of the Russian Federation - ADYGEZALOVA, Gyulnaz Eldarovna; ALLALYEV, Ruslan Muradovich; KISELEVA, Alla Vasilievna; GRIGORIEVA, Natalya Anatolyevna (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).01, 2018)
The article provides an analysis of the features of the legal regulation of copyright protection and the control of the distribution of the prohibited content on the Internet. Copyright violation and distribution of the prohibited content are considered by the author as two sides of the same problem – the illegal use of information on the Internet. Despite the close attention received from legislators, law enforcers, Internet-based businessmen, journalists, bloggers and regular users of Internet resources, the amount of whom is becoming larger from year to year, this problem still remains unsolved up to date, so the urgency of development of its legislative solution is unquestionable. The objective of the work presented is to seek effective legal regulation of Internet relations connected to the protection of authors' rights and the fight against the distribution of illegal (hazardous) content. In order to achieve this objective the author analyses the Russian legislative framework, refers to international and foreign experience and views the positions of representatives of various sciences related to the Internet, especially legal scholars and political scientists. Various categories of Internet-based information, which are regulated under the Russian legal system, are considered in this article. The potential of existing technologies to restrict access to Internet resources is analyzed. The results of the study of different views on the mentioned problems are presented, and solutions for their resolution are offered, which is of scientific and social interest. The scientific novelty and relevance of the study are that in order to address the problem of copyright control and the distribution of illegal content on the Internet, it proposes an integrated approach, combining legislative restriction of access to relevant information with opening an active dialog with the Internet community and business in the area of Internet communications.